First waikavirus infectious clones and vascular expression of green fluorescent protein from maize chlorotic dwarf virus - Stewart, Lucy R.; Willie, Kristen; Xie, Wenshuang; Todd, Jane; Tran, Hong Hanh (Frontiers in Virology, 2023)
Plant viruses classified in the genus Waikavirus, family Secoviridae, are positive sense singlestranded RNA viruses and include important pathogens of maize (maize chlorotic dwarf virus; MCDV) and rice (rice tungro spherical virus; RTSV). Many aspects of the molecular biology of waikaviruses remain unexplored because of experimental challenges and lack of infectious clones for low titer, phloem-limited, and obligately vector-transmitted waikaviruses. Here we report the first development of waikavirus infectious clones for two MCDV strains, MCDV-S and MCDV-M1, and insect-free launching of infections from these clones in maize by vascular puncture inoculation. We further developed a green fluorescent protein (GFP)-tagged MCDV clone by replacing the viral p27encoding sequence with GFP-encoding sequence. GFP-tagged virus moved systemically in plants and caused symptomatic infection similar to wild type virus, with vascular expression of GFP. Development of waikavirus infectious clones is a major advance for this group of agriculturally significant viruses.